Economic effects in the production of sugar beet and sugar - Babović, Jovan; Veselinović, Branislav (Economics of Agriculture, 2010)
The objective of the study is the labor productivity in the production of sugar beet and sugar in three agricultural enterprises on 4. 624 ha. The areas under sugar beet comprised in this study participate with 64 7% in the overall areas under this crop in the region of Srem. The annual production of sugar beet provides for the needs of sugar refineries in total. The basic factors affecting the productivity are: the level of technical equipment, natural factors, the selection of sugar varieties, applied modern technology, the organization of work, the qualification and motivation of the employees. The results can be used for the promotion of business, agro-economic analyses, planning, agro marketing needs and for the comparison of one`s own productivity with the presented results.